Agriculture insurance for disaster risk reduction: A case study of Malaysia - Alam A.S.A.F.; Begum H.; Masud M.M.; Al-Amin A.Q.; Filho W.L. (Elsevier Ltd, 2023)
Malaysia is one of the countries in the Asia-Pacific region that is most vulnerable to hazards such as floods, landslides, droughts, and climate change. Disaster risk continues to grow as a result of unplanned urbanization, persistent poverty, and ecosystem degradation. In this context, insurance is a risk financing mechanism, part of acomprehensive disaster risk management strategy, which plays an important role in disaster risk reduction. Being an economy in transition, Malaysia is in a unique position in relation to agriculture insurance. Based on primary and secondary sources of information and literature review, the present study analyzed the potential effects of agriculture insurance for disaster risk reduction (DRR) in Malaysia. The proposed framework of agriculture insurance suggests the involvement of policy makers and implementers, marketing channels, and micro users for DRR in Malaysia. The study identified challenges for agriculture insurance in Malaysia, such as lack of experience from international practices, limited products, lack of necessary data, limited financial capacity, and high administrative operational costs. Suitable recommendations that aim to promote agriculture insurance and reduce disaster risk in agro-production are offered. These recommendations emphasize proper government initiatives and public-private partnership of insurance companies to assist the market and the designing of suitable insurance products. 2020